2016
DOI: 10.1002/2015jd023777
|View full text |Cite
|
Sign up to set email alerts
|

A unified engineering model of the first stroke in downward negative lightning

Abstract: Each stroke in a negative cloud-to-ground lightning flash is composed of downward leader and upward return stroke processes, which are usually modeled individually. The first stroke leader is stepped and starts with preliminary breakdown (PB) which is often viewed as a separate process. We present the first unified engineering model for computing the electric field produced by a sequence of PB, stepped leader, and return stroke processes, serving to transport negative charge to ground. We assume that a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In most previous IBP modeling studies (e.g., da Silva & Pasko, ; Karunarathne et al, ; Kašpar et al, ; Nag & Rakov, ; Nag & Rakov, ; Shao & Heavner, ), IBPs have been modeled using smooth IBP current waveforms that produce smooth bipolar pulses without any of the subpulses commonly detected on the leading side of the waveform (e. g., Weidman & Krider, ; Stolzenburg et al, ). To be able to include subpulses, we determine the IBP current waveform I ( t ) from the IBP E‐change measurements.…”
Section: Overview Of Ibp Modelingmentioning
confidence: 99%
“…In most previous IBP modeling studies (e.g., da Silva & Pasko, ; Karunarathne et al, ; Kašpar et al, ; Nag & Rakov, ; Nag & Rakov, ; Shao & Heavner, ), IBPs have been modeled using smooth IBP current waveforms that produce smooth bipolar pulses without any of the subpulses commonly detected on the leading side of the waveform (e. g., Weidman & Krider, ; Stolzenburg et al, ). To be able to include subpulses, we determine the IBP current waveform I ( t ) from the IBP E‐change measurements.…”
Section: Overview Of Ibp Modelingmentioning
confidence: 99%
“…Among all lightning flashes, IB pulses were rarely observed in VLF (with >8 dB SNR) at distances greater than a few hundred kilometers, as will be discussed in the next section. Based on this criterion, we have classified the IB radiation reported in this paper (observed at distances greater than a few hundred kilometers) as “intense.” Recent experimental and modeling studies indicate that peak currents producing IB pulses may be as large as several tens of kiloamps [ Karunarathne et al , ; da Silva and Pasko , ; Kolmašová et al , ], flowing over channels with lengths on the order of a few hundred meters to a kilometer [ Stolzenburg et al , , ; Karunarathne et al , ; da Silva and Pasko , ; Nag and Rakov , ]. Such large currents have been demonstrated to produce initial breakdown observable at a distance of 600 km [ Kolmašová et al , , ].…”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…For detailed information regarding the physical nature of IB, we refer the reader to the recent experimental works of Campos and Saba [2013], Stolzenburg et al [2013Stolzenburg et al [ , 2014, and Wilkes et al [2016]. Recent efforts in modeling currents in initial breakdown processes include the works of Karunarathne et al [2014], da Silva and Pasko [2015], and Nag and Rakov [2016].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies of preliminary breakdown by Stolzenburg et al [4,5], who used high-speed video and electric field records, indicated that the PB luminosity bursts were correlated with the PB pulses in the corresponding electric field records and suggested that each PB pulse was caused by a substantial current surge traversing a channel segment of the order of hundreds of meters in length. Nag and Rakov [6], via modeling, estimated the PB pulse peak currents to be of the order of tens of kiloamperes, comparable to or even exceeding the corresponding return-stroke peak current.…”
Section: Introductionmentioning
confidence: 99%